Influence of Influencer Marketing Strategy and Online Customer Reviews on Purchase Intention of Sociolla Customer (Case Study on AB Students at Polines 2018 – 2019) - Qonitah Iffah R; Umar - Farouk; Jati - Nugroho (JOBS (Jurnal Of Business Studies), 2022)
This study aims to determine and analyze the influence of influencer marketing strategies and online customer reviews on purchase intention of Sociolla users. The population in this study were students of the Semarang State Polytechnic Department of Business Administration in the 2018 - 2019 batch, which amounted to 376 students. The number of samples as many as 80 respondents with sampling using purposive sampling technique. The type of this research is quantitative research and data collection in this research is literature study and questionnaires. The scale used in this research questionnaire is the Likert scale. The analytical method used is descriptive analysis, instrument test, classical assumption test, homepage linear regression analysis method, and hypothesis testing. Calculations were carried out using SPSS software. Based on the calculation of the regression equation, namely Y = 0.940 + 0.2740X1 + 0.342X2. So it can be said that influencer marketing (X1) and online customer reviews (X2) have a significant effect on purchase intention (Y).